A Novel Germline Compound Heterozygous Mutation of BRCA2 Gene Associated With Familial Peripheral Neuroblastic Tumors in Two Siblings - Yang, Yeran; Chen, Jiwei; Qin, Hong; Jin, Yaqiong; Zhang, Li; Yang, Shen; Wang, Huanmin; Fu, Libing; Hong, Enyu; Yu, Yongbo; Lu, Jie; Chang, Yan; et al. (Frontiers in Genetics, 2021)
Objectives To investigate the genetic variants that are responsible for peripheral neuroblastic tumors (PNTs) oncogenesis in one family case. Methods One family was recruited, including the healthy parents, sister affected by neuroblastoma (NB) and brother suffered from ganglioneuroma (GN). Whole-genome sequencing (WGS) of germline DNA from all the family members and RNA-seq of tumor RNA from the siblings were performed. Mutants were validated by Sanger sequencing and co-IP was performed to assess the impact of mutant on chemosensitivity in SH-SY5Y cell line. Results A novel compound heterozygous mutation of BRCA2 was locked as the cause of carcinogenesis. One allele was BRCA2-S871X (stop-gain) from the siblings’ mother, the other was BRCA2-N372H (missense) from their father. This novel compound heterozygous mutations of BRCA2 gene associated with PNTs by disordering DNA damage and response (DDR) signal pathway. Moreover, chemosensitivity was reduced in NB cell line due to BRCA2-N372H mutant. Conclusions In summary, these results revealed a novel germline compound heterozygous mutation of BRCA2 gene associated with familial PNTs.